BANK DEPOSIT OPERATIONS AND INTERNAL AUDIT - Kuzieva Lola Erkinovna (Scholar Express Journals, 2023)
This article delves into the crucial aspects of bank deposit operations and the significance of internal audits in ensuring their efficiency and security. Through a systematic exploration of the key components, methodologies, and outcomes, this article aims to shed light on the intricacies of deposit operations within the banking sector, emphasizing the role of internal audit processes in maintaining robust financial systems.
Keywords: Bank deposit operations; internal audit; financial security